Editorial: The rebirth of myeloid-derived suppressor cells: from adversary in cancer to ally in reproductive health. Issue 5 (1st May 2017) - Abrams, Scott I
Abstract : Discussion on how MDSCs are important in maintaining maternal-fetal tolerance, which adds to our understanding of such a longstanding mystery in reproductive biology.